The Effectiveness of The Snowball Throwing Learning Model on Children’s Creativity - Rokyal Harjanty; Sry Anita Rahman; Farlina Hardianti (Lembaga Bale Literasi, 2025)
Early childhood is a period of rapid development that is fundamental to later life. Several common problems in schools include teachers often implementing monotpnous and unvaried learning models. Selecting the right model to enhance the potential of early childhood is crucial to fully develop their abilities. The learning model employed within this research is the snowball casting approach. The pbjective of this investigation is to improve the effectiveness and creativity of children through the snowball –pitching teaching strategy at Mutiara Islami Kindergarten. The type of research in this study, when viewed regarding the research methodology, employs a numerical approach and empirical method. The type of research design one-group pretest-posttest. This study was conducted at Mutiara Islami Kindergarten, located at Citra Mutiara, JL. Banda Seraya No. 12 Block O, Pagutan, Mataram District, Mataram City, West Nusa Tenggara, in the even term of the 2024/2025 scholastic year. The participants in this research was all gade B pupils of Mutiara Islami Kindergarten during the second term of the 2024/2025 scholastic year, comprising of 15 pupils. The posttest learning outcomes after using the snowball throwing learning model on children’s creativity obtained the lowest value of 71 and the highest value of 85, with an average value of 78. So the difference between the pretest and posttest values is 1.6. The outcomes of the computation of the pre-assessment score with a mean of 76,4 and the posttest with a mean of 78, having a total n of fifteen and a significance level of 0.05, obtained an Ltable of 0.22 and L0 of Lhitung of 0.169. Because L0 < Ltable, which is 0.169 < 0.22, then H0 is accepted. Hence, one can infer that the sample is normally distributed. Study outcomes revealed a rise in measurements when comparing baseline data with follow-up results. Hence, one can infer that the snowball throwing academic strategy is effective in increase pupil creativity. This study can be said to be effective if the data obtained shows that pupil learning outcomes have increase when the snowball throwing model is applied.